2015
DOI: 10.1097/rti.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement

Abstract: Transcatheter aortic valve replacement (TAVR) is an increasingly used alternative to surgical aortic valve replacement in patients with severe aortic stenosis and prohibitive perioperative risk. Several studies have shown an improved clinical outcome and lower rate of complications with TAVR in this patient population. Furthermore, TAVR has shown promising results in patients at elevated risk from surgical aortic valve replacement. Because of the endovascular nature of this technique, comprehensive preprocedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…This is the crucial difference from other dual-energy approaches for which a dual-energy acquisition protocol must be defined in advance. Other studies, such as those by Grant et al and Albrecht et al, have shown that CT scanners using other dual-source techniques can be similarly employed for CM reduction [ 26 28 ]. The disadvantage of the dual-layer spectral technology is a slower rotation speed, especially compared to dual-source systems, and the resulting increased radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…This is the crucial difference from other dual-energy approaches for which a dual-energy acquisition protocol must be defined in advance. Other studies, such as those by Grant et al and Albrecht et al, have shown that CT scanners using other dual-source techniques can be similarly employed for CM reduction [ 26 28 ]. The disadvantage of the dual-layer spectral technology is a slower rotation speed, especially compared to dual-source systems, and the resulting increased radiation dose.…”
Section: Discussionmentioning
confidence: 99%